Biocompatible copper sulfide–based nanocomposites for artery interventional chemo-photothermal therapy of orthotropic hepatocellular carcinoma. (September 2021) - Li, X.; Yuan, H.J.; Tian, X.M.; Tang, J.; Liu, L.F.; Liu, F.Y.
Abstract: Transcatheter arterial embolization has been considered as a promising targeted delivery approach for hepatocellular carcinoma (HCC). Currently, chemoembolization was the main treatment for unresectable HCC. However, the traditional chemoembolization treatment suffers from undesirable therapeutic effects and serious side-effects. In this study, the doxorubicin (DOX)-encapsulated and near-infrared (NIR)–responsible copper sulfide (CuS)–based nanotherapeutics was developed for magnetic resonance imaging (MRI)–guided chemo-photothermal therapy of HCC tumor in rats. The DOX-loaded CuS nanocomposites (DOX@BSA-CuS) demonstrated distinct NIR-triggered drug release behavior and high photothermal effect. In an orthotopic HCC rat model, DOX@BSA-CuS nanocomposites were selectively delivered to the tumor site via the intra-arterial transcatheter. The proposed DOX@BSA-CuS nanocomposites plus NIR laser irradiation exhibited significant tumor growth suppression performance. Moreover, the treatment progress can be monitored by MRI images. Finally, the preliminary toxicity estimate suggested the negligible side-effect of DOX@BSA-CuS nanocomposites during the therapeutic process. These results suggest the clinical translational potential possibility for imaging-guided arterial embolization with DOX@BSA-CuS nanocomposites for the treatment of HCC. Graphical abstract: Image 1